Репрезентация категории пространства и времени в языке (лингвистическая характеристика художественного текста). (Eurasian Journal of Philology Science and Education, 2015)
This article discusses linguistic categories of space and time in artistic text. The article presents the analysis of a literary text fragments of works of Russian classics (Ivan Turgenev, Anna Akhmatova Museum poetry, etc.), confirming that the category, representation of space and time is a synthetic, integral to the language. The analysis of representation categories of space and time from a linguistic point of view, the linguistic aspect is based on integration of philosophical concepts-the subject, object, three-dimensional, length, motion; psychological-reference point, the position of the observer, an additional reference points; language-possessive particle-form names are nouns, adverbs, verbs, which reflect the relationship of three concepts of space (an objective, sensible, and language) and provides the opportunity to more fully explore the space and time, from the perspective of its main properties on a text example of fiction.
Keywords: language representation; the categories of space and time in artistic text; semantic; psychological